CHARACTERISTICS AND VARIABILITY OF THE FLORES ITF AND ITS COHERENCE WITH THE SOUTH JAVA COASTAL CURRENT - Agus S. Atmadipoera; Paradita Hasanah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Characteristics and transport variability of the Indonesian Throughflow (ITF) in the western Flores Sea (FS) and its coherency with the South Java Coastal Current (SJCC) fluctuation are investigated using validated ocean general circulation model output (2008-2014) from the INDESO configuration.  The results show that near-surface circulation in the study area is characterized by two distinct regimes:  strong southwestward ITF flow and quasi-transient anti-cyclonic eddies. Vertical dimension of ITF crossing 7.5°S is about 112 km width, 250 m depth, and high velocity core at thermocline >0.3 m/s.  Transport volume estimates along this latitude is -4.95 Sv (southward).  Bifurcation of ITF flow appears north offshore Lombok Island where -2.92 Sv flowing into Lombok Strait and the rest flowing eastward into FS. Meanwhile, vertical dimension of SJCC crossing 114°E is about 89 km width, 120 m depth, and high velocity core at sub-surface >0.35 m/s. Mean transport of SJCC is +2.65 Sv. Coherency between Flores ITF and SJCC transport variability on intra-seasonal scales is significantly high, e.g., on 30 day period (coher=0.92) and phase-lags of 0.6-day with SJCC leading to Flores ITF. This result confirmed previous studies, related to intrusion of coastally trapped Kelvin waves into Flores Sea via Lombok Strait. Keywords: Indonesian Throughflow, western Flores Sea, South Java Coastal Current